Advances in artificial life, evolutionary computation, and systems chemistry : 11th Italian Workshop, WIVACE 2016, Fisciano, Italy, October 4-6, 2016, Revised selected papers /: 11th Italian Workshop, WIVACE 2016, Fisciano, Italy, October 4-6, 2016, Revised selected papers. (2017) - Unknown
No abstract available